Intravitreal slow-releasing dexamethasone implant for idiopathic neuroretinitis - ÇEKİÇ, OSMAN (SAGE PUBLICATIONS LTD, 2022)
Introduction: The purpose of this report is to describe a successful management of idiopathic neuroretinitis with intravitreal dexamethasone implant. Method: Interventional case report. Clinical Case: A 34-year-old man with an acute painless unilateral vision loss, optic disc swelling, and a macular edema was diagnosed as idiopathic neuroretinitis, and he underwent 0.7 mg dexamethasone intravitreous implant injection. Macular edema responded quickly and visual acuity improved from 20/50 to 20/25 within 2 weeks and to 20/20 within a month. One month after the injection, optic disc edema disappeared. No recurrence occurred and visual acuity was stable at 20/20 during 3 years of follow-up. Conclusion: Idiopathic neuroretinitis can be treated with intravitreal dexamethasone implant.
Keywords: Idiopathic neuroretinitis; intravitreal dexamethasone implant; macular edema; optic disc edema